2014
DOI: 10.1089/acm.2012.0499
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and Traditional Chinese Medicine for Hot Flushes in Menopause: A Randomized Trial

Abstract: Acupuncture in an integrated system that includes therapeutic techniques such as diet therapy and Tuina self-massage can be used to treat hot flushes and selected symptoms in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…18 Our feasibility study 19 assessed the effects of acupuncture in a mixed sample of 35 patients with breast cancer experiencing vasomotor symptoms. In accordance with findings from other studies 20,21 at the end of the 10-week treatment period, 66% of patients had a reduction in hot flashes that varied from 50% to 75% compared with baseline. The aim of this study was to investigate the effectiveness of an integrative approach using acupuncture plus enhanced self-care versus enhanced self-care alone for the management of hot flashes in women with breast cancer.…”
Section: Introductionsupporting
confidence: 91%
“…18 Our feasibility study 19 assessed the effects of acupuncture in a mixed sample of 35 patients with breast cancer experiencing vasomotor symptoms. In accordance with findings from other studies 20,21 at the end of the 10-week treatment period, 66% of patients had a reduction in hot flashes that varied from 50% to 75% compared with baseline. The aim of this study was to investigate the effectiveness of an integrative approach using acupuncture plus enhanced self-care versus enhanced self-care alone for the management of hot flashes in women with breast cancer.…”
Section: Introductionsupporting
confidence: 91%
“…29,38,41,44 However, adverse effects, including fatigue, pruritus, nausea, sensitivity to cold, pain, itchiness, low energy, twitching, bleeding at acupoints, and abnormal electrocardiography and white blood cell count, were reported in three trials. 11,14,46 Appraisal of the quality of included studies is reported in Appendix 4, available online at http://links.lww.com/AOG/A760. Only one study achieved a low risk of bias in all domains.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 12 selected articles, eight were categorized as randomized controlled trials [ 30 35 , 39 , 40 ], corresponding to two-thirds of our sample. Among these, only one article had the treatment of sleep disorders as primary aim or outcome [ 35 ], while in the other articles sleep was measured secondarily or indirectly.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, according to the perspective of TCM, the postmenopausal period can be classified as a syndrome, in which sleep disorder may or may not be present, being explained as a consequence of an energetic imbalance. More specifically, in postmenopause there is a marked deficiency of yin , leading to blood and qi stagnation and compromising the balance of kidney, heart, and liver [ 38 , 39 ]. In this case, more than focusing the treatment on the symptoms, TCM prioritizes the treatment of the general root cause (in this case, the postmenopausal syndrome), as it is understood that by treating this root cause, all the consequent symptoms should improve.…”
Section: Discussionmentioning
confidence: 99%